Sex and disease regulate major histocompatibility complex class I expression in human lung epithelial cells - Justine Mathé; Sylvie Brochu; Damien Adam; Emmanuelle Brochiero; Claude Perreault (Physiological Reports, 2024)
Abstract Major histocompatibility complex class I (MHC I) molecules present peptides to CD8+ T‐cells for immunosurveillance of infection and cancer. Recent studies indicate lineage‐specific heterogeneity in MHC I expression. While respiratory diseases rank among the leading causes of mortality, studies in mice have shown that lung epithelial cells (LECs) express the lowest levels of MHC I in the lung. This study aims to answer three questions: (i) Do human LECs express low levels of MHC I? (ii) Is LEC MHC I expression modulated in chronic respiratory diseases? (iii) Which factors regulate MHC I levels in human LECs? We analyzed human LECs from parenchymal explants using single‐cell RNA sequencing and immunostaining. We confirmed low constitutive MHC I expression in human LECs, with significant upregulation in chronic respiratory diseases. We observed a sexual dimorphism, with males having higher MHC I levels under steady‐state conditions, likely due to differential redox balance. Our study unveils the complex interplay between MHC I expression, sex, and respiratory disease. Since MHC I upregulation contributes to the development of immunopathologies in other models, we propose that it may have a similar impact on chronic lung disease.